2017
DOI: 10.1556/0806.44.2016.036
|View full text |Cite
|
Sign up to set email alerts
|

Association between grain yield, grain quality and morpho-physiological traits along ten cycles of recurrent selection in bread wheat (Triticum aestivum L.)

Abstract: The objective of the present investigation was to examine the relationships between agronomical behavior and grain quality along ten cycles of a recurrent selection program performed under rainfed condition. Twenty-four lines, four for each one of the 0, 2, 4, 6, 8 and 10 cycles of recurrent selection, were evaluated for two consecutive years (2011 and 2012). The experimental lines were evaluated under conventional (CT) and no tillage (NT) systems. Grain yield and grain weight were determined and harvest index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…Dwivedi et al, (2017) also reported higher reduction in grain yield (60.3%). Maich et al, (2017) reported elevated temperature caused a reduction in grain yield between 6-21% as compared normal grown varieties. Aynehband et al, (2011) andWang et al, (2017) reported that grain weight depends on different dates of sowing and water availability.…”
Section: Mean Sum Of Squarementioning
confidence: 97%
“…Dwivedi et al, (2017) also reported higher reduction in grain yield (60.3%). Maich et al, (2017) reported elevated temperature caused a reduction in grain yield between 6-21% as compared normal grown varieties. Aynehband et al, (2011) andWang et al, (2017) reported that grain weight depends on different dates of sowing and water availability.…”
Section: Mean Sum Of Squarementioning
confidence: 97%
“…Most self‐pollinated crops, such as common bean ( Phaseolus vulgaris L.), have limitations in crossing systems and in obtaining populations from crosses of several parents at once (Fouilloux & Bannerot, 1988; Sorrels & Fritz, 1982). Instead, breeders carry out several populations by pairwise intercrossing of many parents, achieving relevant success along recurrent selection cycles (Maich, Steffolani, Di Rienzo, & León, 2017; Morais Júnior et al., 2017; Posadas, Eskridge, Specht, & Graef, 2014; Ramalho, Abreu, & Santos, 2005). We refer to this method of recurrent selection as multipopulation recurrent selection (MRS).…”
Section: Introductionmentioning
confidence: 99%
“…Biodiversity conservation in crops, in particular wheat, is one of the greatest challenges facing cereal breeders in the 21st century [1]. Modern bread wheat (Triticum aestivum L.) varieties have to be characterized by high yields, high protein content, as well as high resistance to biotic and abiotic stressors [2].…”
Section: Introductionmentioning
confidence: 99%